If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 5 = 2 + -4(x + 1) Reorder the terms: 5 + 3x = 2 + -4(x + 1) Reorder the terms: 5 + 3x = 2 + -4(1 + x) 5 + 3x = 2 + (1 * -4 + x * -4) 5 + 3x = 2 + (-4 + -4x) Combine like terms: 2 + -4 = -2 5 + 3x = -2 + -4x Solving 5 + 3x = -2 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 5 + 3x + 4x = -2 + -4x + 4x Combine like terms: 3x + 4x = 7x 5 + 7x = -2 + -4x + 4x Combine like terms: -4x + 4x = 0 5 + 7x = -2 + 0 5 + 7x = -2 Add '-5' to each side of the equation. 5 + -5 + 7x = -2 + -5 Combine like terms: 5 + -5 = 0 0 + 7x = -2 + -5 7x = -2 + -5 Combine like terms: -2 + -5 = -7 7x = -7 Divide each side by '7'. x = -1 Simplifying x = -1
| 13(4y-11)=7+5(11y+9) | | x-[9x-(x-8)]=0 | | 7x+17-9x=20-14x+12x-3 | | 4n-8-3n=2n-5 | | X(5x+9)=2x^2-7x+12 | | 2(3-4+5)= | | -1.8=5.1w-2 | | 4x-21=7x+21 | | 10-8x=109-29x | | (4x+5)(5x+4)= | | 48=2x+6 | | 1234567654323456765432345+23454323456543= | | -4y+1=11 | | 5(3x)+10x=6.25 | | 128-5x=4x+20 | | 9x^2+42x-15=0 | | 2x+11=-7 | | 1+5(x-3)=2x-14+3x | | -5s+2=27 | | 3.2-3d=2.3d+3 | | 9d+4d+d+8=5d | | 5x+6-3-4x=10 | | 6t-1=11 | | 5x+10=5+x | | 6+2(x-4)=16 | | ln(x)+ln(3)-ln(6)=ln(10) | | 3x+4=7x-5 | | 4x+8=-3(x-4) | | 9(x+3)-23= | | 4y=z(5-x) | | 14000+160x=24000-200x | | -18=b+2b |